2018
DOI: 10.1177/2151459318764772
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Study of Hip Fractures in the Maltese Islands

Abstract: Introduction:Despite hip fractures being a great public health burden, only few studies have analyzed the relationship between hip fracture incidence and socioeconomic status. Many studies found an association; however, results are in part conflicting.Objective:To analyze the impact of regional-level socioeconomic status on the incidence of hip fractures in the Maltese Islands.Method:All individuals older than 50 years who presented to the acute care hospitals in Malta and Gozo with low-energy hip fractures be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…In another status, they found an increased risk of hip fractures of some socioeconomic indicators and decreased or no association of other socioeconomic markers [34], [38]. However, we may conclude that although it is an important factor, not all the studies found a direct association between the hip fractures and socioeconomic status [39], [40].…”
Section: Discussionmentioning
confidence: 73%
“…In another status, they found an increased risk of hip fractures of some socioeconomic indicators and decreased or no association of other socioeconomic markers [34], [38]. However, we may conclude that although it is an important factor, not all the studies found a direct association between the hip fractures and socioeconomic status [39], [40].…”
Section: Discussionmentioning
confidence: 73%
“…Taking into consideration the ageing of the population and longer life span, the increase in socio-economical loads due to the hip fracture is expected in the future. Therefore, the hip fracture is nowadays considered, not only medical, but also the issue of the entire community (1,6,7,8,18).…”
Section: Discussionmentioning
confidence: 99%
“…Ένα υψηλότερο κατά κεφαλήν ΑΕΠ κατά 10.000 δολάρια ΗΠΑ σχετίστηκε με αύξηση κατά 1,3% της πιθανότητας κατάγματος. Αντιθέτως, οι Bugeja et al (2018) βρήκαν ότι περιοχές στη Μάλτα με κοινωνικο-οικονομική στέρηση είχαν υψηλότερη συχνότητα εμφάνισης του φαινομένου.…”
Section: δημογραφικοι και κοινωνικο-οικονομικοι παραγοντεςunclassified
“…Για κάποιους παράγοντες, όπως η μεγαλύτερη ηλικία (Johansson et al, 2018;Wiklund et al, 2016;Cauley et al, 2016), ο υψηλός αριθμός συνοδών νοσημάτων (Cauley et al, 2016;Reyes et al, 2014), η πολυφαρμακία (Tripathy et al, 2015) κλπ, έχει βρεθεί θετική συσχέτιση. Για κάποιους άλλους παράγοντες κοινωνικο-οικονομικούς (Bugeja et al, 2018;Johansson et al, 2018;Ravindran & Kutty, 2016;Reyes et al, 2015;Quah et al, 2011) και κλινικούς (Ruths et al, 2015;Thorell et al, 2014) (Singh et al, 2016). Μέχρι σήμερα λίγες μελέτες έχουν ερευνήσει το κάταγμα ισχίου κυρίως σε σχέση με τις κοινωνικο-οικονομικές συνθήκες (Bugeja et al, 2018;Johansson et al, 2018;Reyes et al, 2015;Quah et al, 2011), ενώ και η χρήση των ΓΠΣ είναι περιορισμένη στο πεδίο των πτώσεων και των τραυματισμών (Bamzar & Ceccato, 2015;Towne et al, 2015;Morency et al, 2012;Lai et al, 2011;Turner et al, 2009;Lai et al, 2009).…”
Section: ερευνητικά εργαλείαunclassified
See 1 more Smart Citation